2015
DOI: 10.3233/jpd-140365
|View full text |Cite
|
Sign up to set email alerts
|

Side and Type of Initial Motor Symptom Influences Visuospatial Functioning in Parkinson's Disease

Abstract: Background/Objectives Visuospatial problems are common in Parkinson’s disease (PD) and likely stem from dysfunction in dopaminergic pathways and consequent disruption of cortical functioning. Characterizing the motor symptoms at disease onset provides a method of observing how dysfunction in these pathways influences visuospatial cognition. We examined two types of motor characteristics: body side (left or right) and type of initial symptom (tremor or symptom other than tremor). Methods 31 non-demented patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…This information was lacking for some subjects, and had we performed the analysis using four subgroups, the results would probably be meaningless due to the small size of each sample. Due to the exploratory nature of this study and since most imaging studies in PD do not take handedness into consideration ( 9 , 24 , 25 ), we still believe our results are worth reporting. However, we should point that most studies had a predominant right-handed population, and the asymmetric cerebral alterations observed might be due to handedness, and not necessarily side of disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…This information was lacking for some subjects, and had we performed the analysis using four subgroups, the results would probably be meaningless due to the small size of each sample. Due to the exploratory nature of this study and since most imaging studies in PD do not take handedness into consideration ( 9 , 24 , 25 ), we still believe our results are worth reporting. However, we should point that most studies had a predominant right-handed population, and the asymmetric cerebral alterations observed might be due to handedness, and not necessarily side of disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…The d-PD and VaD groups had more difficulty with spatial layout (type C error) possibly because of the greater involvement of basal ganglia lesions disrupting several corticostriatal circuits, which are implicated in visuospatial tasks. 26 In particular, the caudate nucleus and the globus pallidus have been associated with motor planning abilities. 27,28 Disruption of the corticostriatal circuits involving parietal and temporal cortices, which was implied in results related to spatial abilities and visual object recognition, may better explain the role of basal ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…13 The MMSE was administered to evaluate patients' cognitive functioning. 14 According to the severity of cognitive impairment, patients were included in the MCI group (MMSE score: [21][22][23][24][25][26][27][28] or demented group (MMSE score: ≤20). 15…”
Section: Methods Subjectsmentioning
confidence: 99%
“…Declines with age • Declines more than verbal cognitive tasks (Jenkins et al, 2000) • Declines related to changes in underlying neural mechanisms (Klencklen et al, 2012), which involve altered fronto-parietal projections (Drag et al, 2015) Impaired • Can be less impaired than other cognitive domains (Possin, 2010;Caproni et al, 2014) • Associated with increased motor severity and freezing of gait (Nantel et al, 2012) • Related to frontal and parietal lobe deterioration (Biundo et al, 2013), with right hemisphere dysfunction implicated (Karádi et al, 2015;Seichepine et al, 2015) • Underlying structural changes of grey matter in frontal and temporal-parietal cortices impact this function (Pereira et al, 2009;Rektorova et al, 2014) (Unless otherwise stated reported older adult impairments relate to comparison between older adults (>50 years old) and either younger adults or pathological groups, and reported Parkinson's disease impairments relate to comparison to a control group)…”
Section: Declines With Agementioning
confidence: 99%